Influence of the span on the operation of large-span structures - A. K. Yusupov; H. M. Musеlеmov; H. M. Gapparov (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. The purpose of the study is to determine the effect of a span on the operation of large-span structures; the features of the work of large-span coatings, which are widely used in the design and construction of modern buildings and structures, are considered and analyzed.Method. Designs and design techniques are given that allow designing buildings and structures with a large span. Examples of the calculation of a large-span frame are considered, the corresponding drawings are made, nodes and other details are given that can serve as a visual aid in the design of the relevant buildings and structures. Large-span beam trusses and frame systems are considered.Result. The main methods for reducing long-span bending moments, as well as design techniques that reduce span displacements, are proposed and tested.Conclusion. The developed design schemes of frames and trusses provide minimal metal costs, and also allow determining the influence of the parameters and geometry of frames and trusses on metal consumption.